2008
DOI: 10.1002/nau.20566
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ultrasound of the urethral sphincter predicts continence surgery outcome

Abstract: The assessment of the urethral sphincter using a 3D ultrasound scan predicts the outcome of continence surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 41 publications
0
20
0
2
Order By: Relevance
“…This is of significant clinical value as until recently, we have relied mainly upon functional assessments. However, with the progression of simple structural assessments (undertaken by accurate imaging techniques), we may be able to combine this information to influence our choice of management and predict surgical outcomes, as has been previously suggested [14]. However, ours is only a validation study showing normative values in asymptomatic non-pregnant, nulliparous women, and further research in women with lower urinary tract symptoms is needed to assess the clinical role of 3D imaging of the urethral sphincter.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This is of significant clinical value as until recently, we have relied mainly upon functional assessments. However, with the progression of simple structural assessments (undertaken by accurate imaging techniques), we may be able to combine this information to influence our choice of management and predict surgical outcomes, as has been previously suggested [14]. However, ours is only a validation study showing normative values in asymptomatic non-pregnant, nulliparous women, and further research in women with lower urinary tract symptoms is needed to assess the clinical role of 3D imaging of the urethral sphincter.…”
Section: Discussionmentioning
confidence: 89%
“…The role of the urethral sphincter in the pathological development of urinary incontinence has been clearly postulated [12][13][14]. Although the importance of precise structural assessment of the urethral sphincter is paramount, the task of measuring it accurately has recently been met with conflicting opinions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, Khullar et al averaged the bladder wall thickness at the trigone, dome, and anterior bladder wall to develop criteria for detection of detrusor overactivity, others assumed that measurement of the bladder dome is sufficient to define bladder wall thickness, even if they did not find that women with detrusor overactivity had an appreciably thicker bladder wall than other study groups (Khullar et al, 1996;Yang & Huang, 2003). US has also been shown to be a reproducible method of assessing urethral sphincter volume (Digesu et al, 2009). Using 2D ultrasound, on axial US images the normal urethra has a characteristic target-like appearance and is seen as composed by four concentric rings of different echogenicity (Minardi et al, 2007).…”
Section: Ultrasoundmentioning
confidence: 99%
“…Recently Digesu et al showed that three-dimensional ultrasound of the urethral sphincter could predict outcome following Burch colposuspension [11]. Studies on urethral retroresistance pressure (the pressure required to achieve and maintain an open urethral sphincter) have demonstrated contradictory results regarding surgical outcome [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%